Heavy subunit of cell surface Gal/GalNAc lectin (Hgl) undergoes degradation via endo-lysosomal compartments in Entamoeba histolytica. (2nd November 2019) - Verma, Kuldeep; Datta, Sunando
ABSTRACT: The human gut parasite Entamoeba histolytica uses a multifunctional virulence factor, Hgl, a cell surface transmembrane receptor subunit of Gal/GalNAc lectin that contributes to adhesion, invasion, cytotoxicity and immune response in the host. At present, the physiologic importance of Hgl receptor is mostly known for pathogenicity of E. histolytica . However, the molecular mechanisms of Hgl trafficking events and their association with the intracellular membrane transport machinery are largely unknown. We used biochemical and microscopy-based assays to understand the Hgl trafficking in the amoebic trophozoites. Our results suggest that the Hgl is constitutively degraded through delivery into amoebic lysosome-like compartments. Further, we also observed that the Hgl was significantly colocalized with amoebic Rab GTPases such as EhRab5, EhRab7A, and EhRab11B. While, we detected association of Hgl with all these Rab GTPases in early vacuolar compartments, only EhRab7A remains associated with Hgl till its transport to amoebic lysosome-like compartments.